Exploring the Role of CYP3A4 Mediated Drug Metabolism in the Pharmacological Modulation of Nitric Oxide Production - Pérez-del Palacio, José; Díaz, Caridad; Vergara, Noemí; Algieri, Francesca; Rodríguez-Nogales, Alba; de Pedro, Nuria; Rodríguez-Cabezas, M. Elena; Genilloud, Olga; Gálvez, Julio; Vicente, Francisca (Frontiers in Pharmacology, 2017)
Nitric-oxide synthase, the enzyme responsible for mammalian nitric oxide generation, and cytochrome P450, the major enzymes involved in drug metabolism, share striking similarities. Therefore, it makes sense that cytochrome P450 drug mediated biotransformations might play an important role in the pharmacological modulation of nitric oxide synthase. In this work, we have undertaken an integrated in vitro assessment of the hepatic metabolism and nitric oxide modulation of previously described dual inhibitors (imidazoles and macrolides) of these enzymes in order assess the implication of CYP450 activities over production of nitric oxide. In vitro systems based in human liver microsomes and activated mouse macrophages were developed for these purposes. Additionally in vitro production the hepatic metabolites of dual inhibitor, roxithromycin, was investigated achieving the identification and isolation of main hepatic biotransformation products. Our results suggested that for some macrolide compounds, the cytochrome P450 3A4 derived drug metabolites have an important effect on nitric oxide production and might critically contribute to the pharmacological immunomodulatory activity observed.